(untitled) (Journal of Plant Disease Sciences, 2025)
Red rot, caused by Colletotrichum falcatum Went, is the most devastating disease of sugarcane, with widespread occurrence across continents including Asia, Africa, and the Americas. In India, the disease has caused repeated epidemics, severely affecting sugarcane production, particularly in Uttar Pradesh and Bihar. Yield losses ranging from 30% to more than 80% have had a significant negative impact on cane-based economies. The disease is identified by characteristic red lesions in stalk tissues and is strongly influenced by environmental factors such as temperature and humidity. The red rot pathogen survives between cropping seasons through infected plant debris and spreads primarily through infected seed setts and soil, while secondary spread occurs via conidial dissemination by air and water. The emergence of new virulent pathotypes, such as CF13, which infects the widely cultivated variety Co-0238, has resulted in resistance breakdown similar to the vertifolia effect. Management strategies include hot-water treatment, fungicidal sett treatment, soil drenching or drip delivery of fungicides or biocontrol agents, application of bioformulations to soil, foliar sprays during the rainy season, and crop rotation in severely affected areas. However, the use of resistant varieties has been found to be the most effective strategy for disease management. Continuous pathogen evolution necessitates dynamic screening and resistance-breeding programs. Understanding host–pathogen interactions under both natural and artificial conditions is essential to mitigate the threat of red rot in sugarcane ecosystems. This review highlights red rot disease in sugarcane, its impact, and the currently employed management strategies.